Orthoplastic surgery research: Three decades of growth and future directions - Alexander F. Dagi; Michael B. Amrami; Nikhil A. Gangoli; Dylan K. Kim; Jarrod T. Bogue (JPRAS Open)
Six clinical databases were analysed from inception through 2023 to assess the trajectory of orthoplastic surgery research and provide a scoping review of concentrations and gaps in the literature. The literature grew exponentially since 2010, with 66 % of identified studies published between 2020 and 2024. The United Kingdom emerged as the primary contributor, accounting for 47 % of publications following national guideline implementation that demonstrated improved patient outcomes. While meta-analyses support the clinical benefits of orthoplastic management for complex fractures, showing reduced surgical interventions and infection rates, the evidence base relies predominantly on retrospective studies, with no randomized controlled trials identified. Key opportunities to strengthen the field include conducting prospective studies, expanding research beyond lower extremity trauma to areas such as upper extremity reconstruction, oncologic applications, and paediatric care, addressing healthcare access disparities, evaluating cost-effectiveness across different healthcare systems, and developing standardized guidelines beyond the UK.